E-learning project in a science department : an evaluation study of MOREATONCE - Tan, Teck Hock. (2008)
The findings from this research would be used to make decision about continuing, modifying, expanding or accrediting MOREATONCE. It would also help us to understand some of the basic psychological and social implications that may influence the successful implementation of the MOREATONCE e-learning system.